Effects of cycling vs. running training on endurance performance in preparation for inline speed skating - Stangier, C.; Abel, T.; Hesse, C.; Claßen, S.; Mierau, J.; Hollmann, W.; Strüder, H. K. (The Journal of Strength and Conditioning Research, 2016)
Winter weather conditions restrict regular sport-specific endurance training in inline speed skating. As a result, this study was designed to compare the effects of cycling and running training programs on inline speed skaters' endurance performance. Sixteen (8 men, 8 women) high-level athletes (mean ± SD 24 ± 8 years) were randomly assigned to 1 of 2 groups (running and cycling). Both groups trained twice a week for 8 weeks, one group on a treadmill and the other on a cycle ergometer. Training intensity and duration was individually calculated (maximal fat oxidation: ~52% of VO2peak: 500 kcal per session). Before and after the training intervention, all athletes performed an incremental specific (inline speed skating) and 1 nonspecific (cycling or running) step test according to the group affiliation. In addition to blood lactate concentration, oxygen uptake (VO2), ventilatory equivalent (VE/VO2), respiratory exchange ratio (RER), and heart rate were measured. The specific posttest revealed significantly increased absolute VO2peak values (2.9 ± 0.4, 3.4 ± 0.7, p = 0.01) and submaximal VO2 values (p = 0.01). VE/VO2 and RER significantly decreased at maximal (46.6 ± 6.6, 38.5 ± 3.4, p = 0.005; 1.1 ± 0.03, 1.0 ± 0.04, p = 0.001) and submaximal intensities (p = 0.04). None of the analysis revealed a significant group effect (p = 0.15). The results indicate that both cycling vs. running exercise at ~52% of VO2peak had a positive effect on the athletes' endurance performance. The increased submaximal VO2 values indicate a reduction in athletes' inline speed skating technique. Therefore, athletes would benefit from a focus on technique training in the subsequent period.